2019
DOI: 10.3390/su11041156
|View full text |Cite
|
Sign up to set email alerts
|

Association of Carbon Emissions and Circular Curve in Northwestern China

Abstract: Carbon emissions, produced by automobile fuel consumption, are termed as the key reason leading to global warming. The highway circular curve constitutes a major factor impacting vehicle carbon emissions. It is deemed quite essential to investigate the association existing between circular curve and carbon emissions. On the basis of the IPCC carbon emission conversion methodology, the current research work put forward a carbon emission conversion methodology suitable for China’s diesel status. There are 99 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…This prevented measurement error otherwise caused by various factors when directly detecting gas from the exhaust pipe of the test vehicle. The conclusions of this study are comparable with extant results from similar work in other countries; the universal applicability of the research results presented here is guaranteed [15,16]. Data relevant to the extant vehicle fuel characteristics in China can be found in the "National Communication on Climate Change of China" [32,33].…”
Section: Conversion Among Energy Fuel Consumption Carbon Emissionssupporting
confidence: 85%
See 2 more Smart Citations
“…This prevented measurement error otherwise caused by various factors when directly detecting gas from the exhaust pipe of the test vehicle. The conclusions of this study are comparable with extant results from similar work in other countries; the universal applicability of the research results presented here is guaranteed [15,16]. Data relevant to the extant vehicle fuel characteristics in China can be found in the "National Communication on Climate Change of China" [32,33].…”
Section: Conversion Among Energy Fuel Consumption Carbon Emissionssupporting
confidence: 85%
“…The vehicle's energy conversion formulations on downhill road sections in Case I, Case II, Case III are reflected in Equations (13) and 14, Equation 15, Equations (16) and 17, respectively.…”
Section: Symmetrical Slope Combination Roadmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that factors such as fuel, traffic conditions, road gradients, and engine performance have an impact on vehicle fuel consumption and emissions. [22][23][24][25][26] Zhang et al 27 established a multiple regression model that calculated CO 2 emissions considering initial vehicle speed, circular curve length, and roadway segment radius, and they used the field experiment to verify that the Motor Vehicle Emission Simulator (MOVES) model is valid. In addition to the MOVES model, various models have been currently used to estimate vehicle emission factors such as Comprehensive Modal Emissions Model (CMEM), Mobile Source Emission Factor Model (MOBILE), Emission Factor (EMFAC), International Vehicle Emission Model (IVE), and Computer Programme to Calculate Emissions from Road Transport (COPERT) models.…”
Section: Vehicle Emissionmentioning
confidence: 99%
“…The carbon emission data measured by the laboratory dynamometer are unable to reflect on the vehicle's operation on actual roads. Moreover, the default parameters in the models, for instance, vehicle type, fuel characteristics, and weather condition, are not in line with the current status in China, and cannot be directly put to use to predict the carbon emissions of the vehicle on the longitudinal slope sections in China [7,16]. Relevant research on vehicle fuel consumption under certain driving force or vehicle power loads based on vehicle dynamics theory [4,10,11] provides a theoretical basis for establishing a mathematical model of truck's carbon emission on longitudinal slopes in China.…”
Section: Introductionmentioning
confidence: 99%